Detection of the Post-Earthquake Damage in Mamuju Regency in January 2021 Using Sentinel-1 Satellite Imagery - Zulfha Diya Nur Ardzilla; Nia Kurniadin; F. V. Astrolabe Sian Prasetya; Romansah Wumu; Dawamul Arifin; Shabri Indra Suryalfihra (P2M Politeknik Pertanian Negeri Samarinda, 2023)
Friday, January 15 2021 at 02:28:21 Local Time, a tectonic earthquake with a magnitude of 6.2 occurred in Mamuju Regency. The epicenter of the earthquake was on land and at 38 km in depth, 6 km to the northeast of Majene, West Sulawesi Province. This earthquake has damaged buildings such as the West Sulawesi Governor’s Office, the Mitra Manakara Hospital, and landslides at several points on Mamuju – Majene highway. The purpose of this research is to determine the post-earthquake damage that occurred in Mamuju Regency and to find out the area that was detected because of the earthquake. By using Sentinel-1 satellite image data and the change detection method from two Sentinel-1 SAR images, ESA SNAP software is used for data processing by using a threshold classification on the images before and after the earthquake, then converting Raster to Vector, Clip according to the boundaries of Mamuju Regency and Layouts using ArcGIS software. The results of this study are the detection of the post-earthquake damage that occurred in Mamuju Regency of 100.64 km2 (14.78%) total area of damage detected. This research also obtained post-earthquake damage detection maps.